A Modified Intrascleral Intraocular Lens Fixation Technique Using 27-Gauge Blunted Needles with Fewer Intraocular Manipulations. (20th November 2021) - Morino, Kazuya; Iida, Yuto; Akimoto, Masayuki
Abstract : A new method for intraocular lens (IOL) fixation in the scleral tunnel using two common 27G blunted needles and an ultrathin 30G needle with fewer intraocular manipulations was developed. Half-depth scleral flaps were prepared, and vertically angled sclerotomies were performed under each scleral flap, 2 mm from the limbs with a 20G microblade or a 26G needle. Two bent 27G blunted needles connected the sclerotomy and corneoscleral incisions. One haptic was inserted into this bent 27G blunted needle extraocularly and extruded through the sclerotomy site. Each haptic was inserted into the lumen of the preplaced ultrathin 30G needle and buried into the scleral tunnel. In this retrospective study, we reviewed the outcomes of this new technique in patients with at least 3 months' follow-up data. Iris capture of the IOL was not observed in any case, and IOL repositioning was not performed either. Astigmatism induced by intraocular aberration was almost as same as that with other methods. Our technique can be performed in any operation room without any extra instruments. This trial is registered with UMIN000044350 .